A study on the determinants of behavioral intention towards using mobile banking services in Malaysia / Ang Gim Wah - Ang, Gim Wah (2010)
The mobile and wireless market continues to grow at a rapid pace globally, and is considered one of the fastest growing markets in the world. The popularity of mobile communication has transformed electronic banking (wired environment) into mobile banking (wireless environment). This trend contributes the anticipated growth of mobile financial solutions as many financial institutions are very excited about the great potential of mobile banking with its large pool of users. Location and time will no longer constrain people from completing their banking transactions using mobile banking services. Therefore, the objective of this study is to examine the extent of acceptance of mobile banking by its customers and to determine the factors that would influence the behavioral intentions to use for financial transactions in Malaysia. A questionnaire survey was conducted with the banking customers as the respondents. The results indicate that the importance of perceived usefulness as the determinants of behavioral intention to adopt mobile banking. The results also further reveal that perceived ease of use, perceived credibility, behavioral control and attitude are significant factors in explaining the acceptance of mobile banking. On the other hand, the findings also indicate that subjective norms and perceived risk were not significantly related to behavioral intention to use mobile banking. The results of this study support the theoretical framework and the finding provides a better understanding of customer perceptions of mobile banking services to the financial services industry. It could also assist them to plan their marketing strategies for mobile banking services in the future.